1997
DOI: 10.3354/meps154175
|View full text |Cite
|
Sign up to set email alerts
|

Significance of body size in sulphide detoxification in the Baltic clam Macoma balthica (Bivalvia, Tellinidae) in the Gulf of Gdansk

Abstract: The Baltic clam Macoma balthica, a predominant species of macrofauna in the Gulf of Gdansk (Poland), is exposed to high concentrations of hydrogen sulphide at many locations in this bay. When oxygen is available, the species is able to detoxify penetrating sulphlde mainly by oxidizing it to non-toxlc thiosulphate. Sulphide influx rato can be quantified by calculation of the diffusion coefficient for total sulphide. A relatively low apparent diffusion coefficient of about 2 X 10 cm' S' l indicates that M. balth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Although there are some limits to the degree to which the different diffusion coefficients can be compared (cf. Jahn et al 1996Jahn et al , 1997, it seems plausible that species with shells are able to reduce sulphide diffusion by temporary reduction of valve opening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are some limits to the degree to which the different diffusion coefficients can be compared (cf. Jahn et al 1996Jahn et al , 1997, it seems plausible that species with shells are able to reduce sulphide diffusion by temporary reduction of valve opening.…”
Section: Discussionmentioning
confidence: 99%
“…in detail in Jahn (1997) and Jahn et al (1996Jahn et al ( , 1997 H~ddensee with the following equations: r,2…”
Section: Animalsmentioning
confidence: 99%
“…From the nematode species Oncholaimus campylocercoides living at shallow-water hydrothermal vent sites off the Greek Island Milos, Thiermann et al (2000) reported that its sulphide tolerance under hypoxic conditions became greatly reduced when ambient sulphide levels reached 1 mmol l -1 . Powell (1989) and Jahn et al (1997) calculated that, depending on the ambient sulphide concentration, diffusive sulphide flux into the body tissue of small-sized organisms can be very fast, literally flooding them and overriding any detoxification mechanisms. We propose that, in the Hydrate Ridge microbial mat sediments overlying shallow gas hydrates, the adaptive capability of nematodes is exhausted due to extremely high sulphide concentrations coupled with limited oxygen availability.…”
Section: Meiobenthos At Microbial Mat Sitesmentioning
confidence: 99%
“…Sulphur peaks (often together with metals), recorded in granules or intracellular inclusions in various non-bacteria-symbiotic meiobenthic and rnacrobenthic fauna, have led to the suggestion that elemental sulphur or insoluble metal sulphides, accumulating in the body, are the results of H2S detoxification (Powell et al 1980, Nicholas et al 1987, Giere et al 1988. However, these and other studies could not convincingly document the effective export mechanisms required to remove the inclusions from the tissues (Somero et al 1989 (Powell 1989, Jahn et al 1997.…”
Section: Formation Of Sulphur Inclusionsmentioning
confidence: 91%
“…By theoretical deduction and exanoxic/sulphidic conditions (Por & Masry 1968). Since in perimental scrutiny, Jahn et al (1997) confirmed that that experiment oxygen or sulphde concentrations have animals smaller than 1 mm are 'not able to detoxify not been recorded, a comparison to the data on 011-hydrogen sulphide effectively enough but rather can cholaimus campylocercoides is not possible. Also various only survive in sulphidic habitats due to their anaeroscattered reports on, freshwater and marine nematodes bic capacity'.…”
Section: Ecophysiologymentioning
confidence: 93%